Schizophrenia: effects of aripiprazole in metabolic syndrome - Deborah Galvão Coelho da Silva; Luiz Kae Sales Kanazawa; Débora Dalla Vecchia (Universidade de São Paulo, 2019)
Schizophrenia, in general, is characterized by severe and disabling mental alterations, characterized by the impairment of one's mental, behavioral and social activities, developing certain clinical symptoms, relevant to the diagnosis. The drugs used for the reversion of the symptoms cause several adverse effects that affect the patient's health and well-being, such as motor, endocrine and cardiovascular damages. For a long time, little was known about the origin and the treatment of schizophrenia, which has become a curiosity for science, originating countless researches and theories that are background for several treatments. It is known that alterations in dopaminergic pathways are related to the development of the symptoms of the disease, and evaluating these symptoms, the diagnosis is made and the treatment is initiated. The insertion of new drugs with different characteristics and mechanisms tends to be an advance in the treatment of schizophrenia, as well as reducing the occurence of adverse effects or not worsening already existing cases. Aripiprazole is an innovative atypical antipsychotic employed in the pharmacotherapy of schizophrenia, which tends to attenuate the symptoms, inducing few adverse effects compared to other drugs that are already used, and promotes better quality of life to patients.